PENGEMBANGAN STRATEGI BISNIS BERKELANJUTAN PADA PETERNAKAN SAPI PERAH DENGAN TRIPLE LAYERED BUSINESS MODEL CANVAS - Hariyati, Yuli; Syahroni, Maulid Dia Putri; Agustin, Dwi; Kamila, Tati Zulfa; Nurlaili, Nurlaili; Ria, Vina Yunita (PAPUMA: Journal of Community Services, 2025)
Rembangan Dairy Farm, located in Jember Regency, East Java, is a dairy farming business that has been operating since 1932 and is managed by the local government under the Department of Food Security and Livestock. The farm focuses on producing high-quality fresh cow's milk with a fat content of 3.69%-4.13% and also offers educational tourism for the public. This study employs the Triple Layered Business Model Canvas (TLBMC) approach to analyze the sustainability of the farm from economic, social, and environmental perspectives. The analysis reveals that the economic aspect scores 68.47, with weaknesses in partner collaboration (Key Partners) and core activities (Key Activities). The social aspect achieves the highest score (76.25), but further adaptation to local culture (Societal Culture) is needed. Meanwhile, the environmental aspect scores the lowest (29.13) due to negative impacts such as the use of plastic packaging and suboptimal waste management. To enhance sustainability, Rembangan Dairy Farm is advised to strengthen partnerships, improve customer service, and implement environmentally friendly strategies, such as the use of sustainable raw materials and better waste management. Through these steps, Rembangan Dairy Farm is expected to enhance its competitiveness, improve community welfare, and reduce environmental impacts, thereby making a greater contribution to the national dairy industry.